Genetic diversity of late Neanderthals in northwestern Europe - Alba Bossoms Mesa; Elena Essel; Stéphane Peyrégne; Arev P. Sümer; Leonardo N. M. Iasi; Christian Heide; Divyaratan Popli; Cesare de Filippo; Marie-Theres Gansauge; Lars Gerullat; Laurin Lippik; Sarah Nagel; et al. (Nature, 2026)
Abstract Archaeological, osteological and genetic evidence suggests that Neanderthals lived in small groups 1,2 ; however, less is known about whether these groups were part of isolated communities or belonged to larger, well-connected populations 3 . The dense concentration of broadly contemporaneous Neanderthal sites in the Meuse Basin, Belgium 4 , provides a rare opportunity to study regional populations at high resolution. Here we generated genetic data from 27 Neanderthals who lived less than approximately 52,500 years ago from ten archaeological sites in Belgium and France, including a high-coverage genome from a 45,000-year-old individual from Goyet, Belgium. We show that most of these individuals are more closely related to one another than to other contemporaneous late Neanderthals in Europe. Further, some of these individuals carry DNA from a Neanderthal lineage predating the split of late Neanderthals. Although these Neanderthals overlapped temporally with early modern humans in northwestern Europe from around 47,000 years ago, we find no evidence of recent gene flow from modern humans. They also do not show the genetic signatures of mating among close relatives found in Altai Neanderthals, suggesting that they lived in larger or better-connected groups. Moreover, genetic load did not accumulate over time, arguing against progressive genetic deterioration as a driver of Neanderthal extinction.